The Development of Evaluation Instruments in Online Learning using the Quizizz Application: During Covid-19 Pandemic - Sri Haryati; Sri Wilda Albeta; Dedi Futra; Anggi Desviana Siregar (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to produce an online learning evaluation instrument that is considered feasible by material experts, evaluation experts and through item analysis and user response questionnaires. This research was conducted with a 4D development model. The instruments used in this study were the material expert's feasibility assessment sheet, evaluation expert, item analysis and user response questionnaires, namely lecturers and students. The data analysis in this study used a rating scale and the item analysis used the product-moment, Kuder-Richardson, the discrimination power and the difficulty level of the questions. Through the item analysis of the 25 questions selected 10 questions that meet the discrimination power,difficulty level, validation and reliability. The reliability coefficient is 0.851 which is classified as high reliability. Meanwhile, the evaluation of material experts was 85.4%, expert evaluation was 88%, student response was 90.7% and lecturers were 90%. Based on the feasibility content, the overall learning evaluation instrument using the quizizz application is declared feasible.